Effect of palm oil fuel ash (Pofa) on the durability of asphaltic concrete - Maleka, Abdulmalik Musa (2015)
The Cantabro durability test is usually used for open graded asphalt mixtures and has seen little use with dense graded mixtures. This paper presents durability data from the Cantabro test for Palm oil fuel ash (POFA) modified dense graded asphaltic concrete AC 14. The nature and amount of filler in an asphaltic concrete mixes significantly affect its design and performance. POFA is an ash obtained from the burning of waste material generated from the production of crude palm oil which is of high quantity in Malaysia. A number of trial mixes were prepared using the Marshall Mix design procedure with 5% POFA and 1% Ordinary Portland Cement (OPC) as filler materials to arrive at asphalt concrete mixtures that fulfil the Marshall criteria. Cantabro durability test was used to measure the durability of the asphaltic concrete. The results show that Marshall stability, flow, stiffness and cantabro loss values shows general improvement for the POFA modified asphalt compared to the control specimens.